2015
DOI: 10.12816/0019006
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intrinsic and Extrinsic Rewards on Employee Motivation at a Medical Devices Company in South Africa

Abstract: In a competitive business environment, the concept of rewards and employee motivation has become a popular point of discussion in many successful organisations. Companies need to review their reward systems in order to improve employee motivation, increase performance and stay competitive. The main purpose of this research was to investigate the role that intrinsic and extrinsic rewards play in motivating employees. This study in assessment of this problem adopted an explanatory research design using quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 43 publications
0
19
0
4
Order By: Relevance
“…respectively. The motivation of employees was measured by pooling and adopting measures from Oyedele (2010), Cerasoli et al (2014), Smith (2015) and Yousaf, et al (2015). Its construct reliability was 0.83.…”
Section: The Measuresmentioning
confidence: 99%
“…respectively. The motivation of employees was measured by pooling and adopting measures from Oyedele (2010), Cerasoli et al (2014), Smith (2015) and Yousaf, et al (2015). Its construct reliability was 0.83.…”
Section: The Measuresmentioning
confidence: 99%
“…Financial rewards may lead to negative effect on employees when goals are now achieved, such as a lack of confidence or being demotivated [11]. In the other hands the provision such as health insurance and pension benefits seem to have a good overall motivational effect on employees, so they have willing to increase work efforts in order to gain rewards [12]. employees and motivate to have a positive impact on the organization [13].…”
Section: A Rewardsmentioning
confidence: 99%
“…Motivation is the driving force leads individuals to want to act, perform, or do something without pressure or manipulation [12]. It is an accumulation of different process that influence and direct our behaviour to achieve some specific goal [2].…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrinsic motivation is defined as a psychological force that impels employees to perform based on an aspect of nature that is expressed under certain conditions (Gyamfi, 2014). Recent studies have found that employees would most value a job that has aspects that are important and meaningful to them rather than extrinsic rewards (Smith, Joubert, Karodia, 2015). According to Ryan and Deci (2017) when high levels of intrinsic motivation are provided employees, may lessen their need for extrinsic rewards.…”
Section: Employee Motivation Intellectual Stimulation and Employee Ementioning
confidence: 99%